Uso da cinza de resíduo urbano em cerâmicas vermelhas - Graupmann, Olaf (2022)
In contemporary times, a high rate of urban solid waste is produced, which brings unwanted consequences for the human being, as well as the entire environment. It is understood the need to mitigate the amount of solid waste deposited in nature, causing environmental problems, which may undergo a process of “burning” (gasified) turned into ash. After this process, it can be used in civil construction as a component for the manufacture of new products, by replacing a percentage of certain raw materials. The study aims to develop products for civil construction in ceramics that use industrial waste such as: waste glass, blast furnace slag, foundry sand, ash from urban solid waste and natural clay and, at the same time that they meet the properties of ceramic products used in civil construction. To carry out the research, the experimental research method was used, in which physical, chemical and thermal tests were carried out, among which: FRX, DRX, SEM, EDS, and resistance tests in flexural compression. After the research was carried out with different compositions, with the use of residues, in ceramics, it was observed that most of the compositions tested reached satisfactory results, the composition that reached the best results was the mixture with 75% of residues and only 25% of natural clay. Compositions containing ash had an increase in strength and good water absorption.